Consumer Expectations Toward of the Apple Store Application in Lat Krabang District, Bangkok - ดาวขาว, ทักษพร; ฐิติเศรษฐากุล, พิสิษฐ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were (1) to study the consumer expectations toward the use of the Apple Store application in Lat Krabang District, Bangkok., (2) to examine the quality and expectations regarding the use of the Apple Store application among consumers in Lat Krabang District, Bangkok., and (3) to study the marketing mix factors related to consumer expectations toward the use of the Apple Store application in Lat Krabang District, Bangkok.The sample in this study is consumers who buy art toy blind boxes living in Minburi, Bangkok. 400 people using a questionnaire as a tool to collect data. The data obtained from the questionnaire was analyzed using statistics. Arithmetic mean () and Standard Deviation (S.D) were used to test the hypothesis using t-test, F-test (One-Way ANOVA) and Multiple Linear Regression Analysis with a statistical significance level of 0.05.           The results of the study revealed that the majority of respondents were female, aged between 21 and 30 years old. Most held a bachelor's degree, were employed in the private sector, and had an average monthly income ranging from 15,001 to 20,000 Baht. In terms of the quality and consumer expectations toward the use of the Apple Store application in Lat Krabang District, Bangkok., it was found that respondents generally had a high level of positive perception, with an overall mean score of 3.96. Among the various dimensions assessed, reliability received the highest rating with a mean score of 4.02, followed closely by user expectations (3.99), trust and security (3.98), responsiveness (3.94), and convenience and accessibility (3.88), all of which were rated at a high level.           Furthermore, when examining the marketing mix factors influencing consumer expectations toward the use of the Apple Store application, the findings indicated an overall high level of agreement, with an average score of 3.90. Specifically, the product dimension received the highest score at 4.00, followed by physical evidence (3.95), process (3.92), people (3.88), distribution channels (3.86), price (3.86), and promotion (3.83). These results reflect a consistently high level of consumer expectation across all aspects of both service quality and marketing mix variables.           The study revealed that personal factors-specifically educational level and monthly incomehad a statistically significant effect on consumer expectations regarding the use of the Apple Store application in Lat Krabang District, Bangkok, at the 0.05 level of significance. Consumers with different levels of education and income demonstrated significantly different expectations toward the application and its services. Moreover, the analysis of marketing mix factors indicated that several dimensions had a statistically significant influence on consumer expectations. Among these, the product factor had the greatest impact (B = 0.287, Sig. = 0.000), followed by price (B = 0.205, Sig. = 0.000) and promotion (B = 0.146, Sig. = 0.000). Additional significant influences were found in the areas of personnel (B = 0.094, Sig. = 0.004), distribution channels (B = 0.080, Sig. = 0.007), process (B = 0.076, Sig. = 0.042), and physical evidence (B = 0.061, Sig. = 0.029). All of these variables were statistically significant at the 0.05 level.